Effect of Coating Thickness on the Properties of TiN Coatings Deposited on Tool Steels using Cathodic ARC PVD Techique - Mubarak, A.; Akhter, Parvez; Hamzah, Esah; Mohd. Toff, Mohd. Radzi; A. Qazi, Ishtiaq (World Scientific, 2008)
Titanium nitride (TiN) widely used as hard coating material, was coated on tool steels, namely on high-speed steel (HSS) and D2 tool steel by physical vapor deposition method. The study concentrated on cathodic arc physical vapor deposition (CAPVD), a technique used for the deposition of hard coatings for tooling applications, and which has many advantages. The main drawback of this technique, however, is the formation of macrodroplets (MDs) during deposition, resulting in films with rougher morphology. Various standard characterization techniques and equipment, such as electron microscopy, atomic force microscopy, hardness testing machine, scratch tester, and pin-on-disc machine, were used to analyze and quantify the following properties and parameters: surface morphology, thickness, hardness, adhesion, and coefficient of friction (COF) of the deposited coatings. Surface morphology revealed that the MDs produced during the etching stage, protruded through the TiN film, resulting in filmwith deteriorated surface features. Both coating thickness and indentation loads influenced the hardness of the deposited coatings. The coatings deposited on HSS exhibit better adhesion compared to those on D2 tool steel. Standard deviation indicates that the coating deposited with thickness around 6.7 Î¼m showed the most stable trend of COF versus sliding distance.